Volition completes the puzzle: Development and evaluation of an integrative trait model of self-regulated learning - Dörrenbächer, Laura; Perels, Franziska (Frontline Learning Research, 2015)
Most self-regulated learning theories are imbedded within a social-cognitive framework and comprise cognitive, metacognitive and motivational components. Nevertheless, these theories partly neglect volition, which is necessary for implementing learning intentions. Therefore, the present study is frontline as it aimed to integrate volition within a comprehensive trait model of self-regulated learning (SRL) while proposing a new conception of trait volition for learning. A sample of n = 377 college students (70.1% female, MAge = 23.36, SDAge = 4.12) filled out questionnaires concerning volitional, cognitive, metacognitive, and motivational belief aspects of SRL. The results of confirmatory factor analysis speak in favour of integrating the highly interrelated constructs of procrastination, future time perspective, and academic delay of gratification in order to depict volition for SRL. Moreover, the structural equation modelling results favour a twofold motivational component for SRL that comprises both motivational beliefs and volition instead of including volition as a separate component aside from cognitive, metacognitive and motivational belief components. Additionally, the comprehensive trait model of SRL is related to GPA, which is a first indication of its validity. Therefore, the study empirically investigates a new conception of trait volition for learning environments as well as its integration within a comprehensive SRL framework. Future research should consider the importance of volitional components for SRL and could investigate individual differences concerning the modelled components.